Identification of Rock Resistivity and Slip Surface in the Ambon Volcanic Rock in the Kayu Putih Area of Ambon City - Latupapua, Andrias Izaac; Puturuhu, Ferad; Marthen, Maylsea Camay (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Research on rock resistivity and slip surface in the Ambon Volcanic Rock formation has been carried out through geoelectric mapping with the Wenner-Schlumberger configuration in the Kayu Putih area, Ambon City as one of the areas prone to landslides. Measurement of rock resistivity by Mapping was carried out on two tracks each 120 m long and 70 m long intersecting each other. The results showed that the resistivity values ​​of the rocks ranged from 185 Ωm to 4,128 Ωm consisting of Top Soil, Unsaturated Landfill, and Loose Sand as the cover layer followed by Dry Sandy Soil and Gravel, and Breccia Dacite and Tuff at the bottom layer. Breccia Dacite rocks with a resistivity of greater than 2,000 Ωm are found at a depth of 11 – 13 m below the soil surface functioning as slip surface for the sand layer above them. The movement of the soil mass over the slip surface causes cracks in the surface of the road and houses.